2020
DOI: 10.1021/acs.orglett.0c01924
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced α-C(sp3)–H Acetalization of Saturated Heterocycles Catalyzed by a Dimeric Gold Complex

Abstract: Saturated heterocyclic acetals are useful fragments in organic synthesis and other fields. Herein, C­(sp3)–H dehydrogenative cross-couplings of ethers, tetrahydrothiophenes, and pyrrolidines were achieved under visible light irradiation by using iodobenzene and an in situ-formed gold complex. The broad functional group compatibility and substrate scope indicate that our strategy is a promising way to synthesize acetal analogues. The method was successfully applied in late-stage modifications of bioactive molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…After demonstrating the feasibility of an energy transfer reaction by using the dinuclear gold­(I) catalyst, the Hashmi group exploited this promising technique further and disclosed a C­(sp 3 )–H acetalization of saturated heterocycles ( 367 ) (Scheme ). Acetals derived from cyclic ethers are highly applicable motifs , and can be found in several drugs (e.g., epirubicin, streptomycin). Herein, diverse alcohols for the acetalization of ethers were examined and further expanded to thioethers and amides.…”
Section: Dinuclear Gold Catalystmentioning
confidence: 99%
“…After demonstrating the feasibility of an energy transfer reaction by using the dinuclear gold­(I) catalyst, the Hashmi group exploited this promising technique further and disclosed a C­(sp 3 )–H acetalization of saturated heterocycles ( 367 ) (Scheme ). Acetals derived from cyclic ethers are highly applicable motifs , and can be found in several drugs (e.g., epirubicin, streptomycin). Herein, diverse alcohols for the acetalization of ethers were examined and further expanded to thioethers and amides.…”
Section: Dinuclear Gold Catalystmentioning
confidence: 99%
“…In the past decade, photocatalytic radical coupling reactions have been reported for the generation of radical species under mild conditions. For example, Fu et al reported a photoinduced radical C–S bond formation reaction using a photocatalyst. More recently, an electron donor–acceptor (EDA) complex was developed for use in the visible-light-driven photoreaction instead of photocatalysts because EDA complexes often absorb visible light. Miyake et al reported a visible-light-driven C­(sp 2 )–S bond formation reaction via the EDA complexes of aryl thiols and aryl halides (Figure b), wherein reactive radical species are generated by single electron transfer (SET) from the EDA complexes. On the other hand, the reactive radical species can abstract a C­(sp 3 )–H hydrogen atom (hydrogen atom transfer: HAT ) to give alkyl radical species. By utilizing these phenomena, novel photoreactions via EDA-SET and HAT combination are achieved. …”
Section: Introductionmentioning
confidence: 99%
“…Except from the use of metals, the synthesis of 2-alkoxy-tetrahydrofuran has also been reported with n-tetrabutylammonium peroxy-disulfate; however, excess of the reagents were used, limiting the green character of the method [16]. Two photocatalyzed iodine-based methods were recently developed by Toste [17] and Hashmi [18] (Scheme 1, B and C). Toste and coworkers described the use of a chiral diaryliodonium phopshate to generate controlled diastereoselective cis-or trans-fused acetals (Scheme 1, B) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Toste and coworkers described the use of a chiral diaryliodonium phopshate to generate controlled diastereoselective cis-or trans-fused acetals (Scheme 1, B) [17]. More recently, Hashmi and coworkers showed that under visible light irradiation and using a dimeric gold complex lead to the formation of the desired acetals of tetrahydrofuran (Scheme1, C) [18].…”
Section: Introductionmentioning
confidence: 99%